GDF15 controls primary cilia morphology and function thereby affecting progenitor proliferation - Baur, Katja; Şan, Şeydanur; Hölzl-Wenig, Gabriele; Mandl, Claudia; Hellwig, Andrea; Ciccolini, Francesca (Life science alliance, 2024)
We recently reported that growth/differentiation factor 15 (GDF15) and its receptor GDNF family receptor alpha-like (GFRAL) are expressed in the periventricular germinal epithelium thereby regulating apical progenitor proliferation. However, the mechanisms are unknown. We now found GFRAL in primary cilia and altered cilia morphology upon GDF15 ablation. Mutant progenitors also displayed increased histone deacetylase 6 (Hdac6) and ciliary adenylate cyclase 3 (Adcy3) transcript levels. Consistently, microtubule acetylation, endogenous sonic hedgehog (SHH) activation and ciliary ADCY3 were all affected in this group. Application of exogenous GDF15 or pharmacological antagonists of either HDAC6 or ADCY3 similarly normalized ciliary morphology, proliferation and SHH signalling. Notably, Gdf15 ablation affected Hdac6 expression and cilia length only in the mutant periventricular niche, in concomitance with ciliary localization of GFRAL. In contrast, in the hippocampus, where GFRAL was not expressed in the cilium, progenitors displayed altered Adcy3 expression and SHH signalling, but Hdac6 expression, cilia morphology and ciliary ADCY3 levels remained unchanged. Thus, ciliary signalling underlies the effect of GDF15 on primary cilia elongation and proliferation in apical progenitors.
Gesehen am 04.11.2024